THE RECOGNITION AND PROTECTION OF INDIGENOUS PEOPLES’ RIGHTS WITHIN THE FRAMEWORK OF REGIONAL AUTONOMY IN INDONESIA - Afif Syarifudin Yahya (Natapraja, 2025)
This research investigates how Indonesia’s decentralization framework affects the recognition and protection of Indigenous communities’ entitlements. Using qualitative methods with a normative juridical, the research analyzes the prevailing legal provisions (Article 18B (2) of the 1945 Constitution, Law 23/2014, Law 6/2014, Law 41/1999, Law 5/1960), and Regional Regulations. In addition, interviews are used to determine the effectiveness of implementation, selected based on criteria (policy makers, policy implementers, and affected indigenous communities). The informants involved in this research consisted of 17 individuals, including: Head of Wali Nanggroe, Head of Civil Registration Officials, Head of Community Empowerment Services, Head of Sub-District, Head of Village, Head of Traditional Institution, and Traditional Figures.The findings reveal that although Indigenous Peoples are constitutionally recognized, implementation at the regional level still faces various challenges, such as weak harmonization between central and regional regulations, and limited understanding by regional governments regarding the substance of Indigenous rights. Several regional governments have not issued specific regional regulations concerning the recognition of Indigenous Peoples or face obstacles in their implementation. This research recommends the need to strengthen legal policies that support the recognition and protection of Indigenous rights through intergovernmental synergy and the enhancement of institutional capacity at the regional level.